Legend, Myth, and Magic in the Image of an Artist: A Historical Experiment - Kris, Ernst; Kurz, Otto; Gombrich, Ernst 1909-2001 (New Haven, CT London Yale University Press, 1979)
This is the first English translation of a brief, scholarly, and brilliantly original work which sets out to examine the links between the legend of the artist, in all cultures, and what E.H. Gombrich, in an introductory essay, calls certain invariant traits of the human psyche.Denis Thomas, Journal of the Royal Society of ArtsThis book gathers together various legends and attitudes about artists, ancient and modern, East and West, and gives fascinating insights into attitudes toward artistic creation. It impinges on psychology, art history and history, aesthetics, biography, myth and magic, and will be of great interest to a wide audience in many fields&. A delightful and unrivalled study.Howard HibbardThought provoking and valuable&. To all those interested in psychiatry and art from the perspectives of history, criticism, or therapy and to the wide audience concerned with the psychology of aesthetics and of artistic creation.Albert Rothenberg, American Journal of PsychiatryErnst Kris was a psychoanalyst who wrote on a wide variety of subjects, including art.Otto Kurz was librarian of the Warburg Institute in London.The text (originally, a German-language contribution) was written by two very young scholars whose bold thesis is in many ways representative of the brilliant inquiries of modernist thinkers between the two World Wars (when a whole generation of Western intellectuals--including the highly articulate proponents of Surrealism--had fully absorbed the ground-breaking psychological researches of Freud and Jung). Kris and Kurz's thesis is that our modern ideas about what makes artists tick (inspiration, genius, eccentricity, neurosis or even madness, technical wizardry, etc.) have a very ancient and widespread ancestry. They correspond, to a greater or lesser extent, to a transcultural, and composite "artist type" (the different elements do not form a seamless whole, but arise from diverse and overlapping traditional understandings of the skills required for art-making) whose features can be found--as the title suggests--in ancient mythic and legendary material, and can be traced into the documented history of art, down to our own day. Rather than claiming outright that the "image" of The Artist is an archetype reembodied in every authentic flesh-and-blood artist, Kris and Kurz leave us with the more interesting possibility that individual artists, whether trained in a tradition that exalts personal talent, or one that rewards collaborative effort (and likewise the far more numerous viewers of their art), all inherit the composite "artist-template" and are molded by it in one way of another, according to the specific expectations of their particular social world. The authors cite a wealth of anecdotal material surviving in ancient European and Asian literary sources, establish its connections with Early Modern artistic biography, and also draw on anthropological material then becoming available to them. The book is not an "easy read," but it is concise and to the point (the opening chapter lays out all of the main arguments and rewards careful reading), and filled with marvelous examples of the special roles artists are, even now, called upon to play.
Keywords: Fine art; Mythology; Cuckoo